Fast computation of invariant geometric moments: a new method giving correct results - Yang, L.; Albregtsen, F. (Pattern Recognition, 1994 12th International Conference On. Vol. 1, 1994)
Invariant geometric moments have been widely used in shape analysis and pattern recognition. Using a discrete version of Green's theorem, the authors propose a method for fast computation of the moments in binary images. The method is similar to-and as efficient as-the previous method of Li and Shen (1991). But the precision is largely improved. The new method gives exactly the same results as if the moments were computed by direct summation over the object area.